THE POWER OF LOVE IN NATHANIEL HAWTHORNE’S RAPPACINI’S DAUGHTER - Ngantung, Lovely Ginesa; Mamentu, Agustine C.; Maukar, Merlin M. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
This research has the purpose of investigating the power of love in Nathaniel Hawthorne’s Rappacini’s Daughter. This research is in the form of qualitative which resulting the outcome to be in the form of words. The data comes from Nathaniel Hawthorne’s Short Story entitled “Rappacini’s Daughter” which was published in 1844. In administering this research, psychological approach is the most suitable to be used and was implemented in order to discover the power of love in the literary works through id, ego and superego. The result of the study explains how the power of love occurred through the id, ego and superego from the characters in the short story. It can be concluded that the characters in Rappacini’s Daughter indeed expressed their power of love through their intimacy which is id, passion which is ego and commitment which is superego which can be said as the components of the power of love